Path Mechanism to reduce packet data loss in Wireless Mesh Networks - Singh, Rajinder; Bhalla, Er. Nidhi (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
A wireless mesh network (WMN) is a communicationnetwork made up of radio nodes organized in a meshtopology. Wireless mesh network often consists of meshclients, mesh routers and gateways. A wireless Mesh networkuses multi-hop communication. Due to multi-hop architectureand wireless nature, Mesh networks are vulnerable to varioustypes of Denial of Services attack. It suffers from Packetdropping at Routing layer. Client nodes are unable to getservices from gateway nodes, hence network gets down. ThePaper emphasis on the developing of a path protocol when theminimun possible packet dropp occurs in wireless meshnetworks. Due to packet droping occurrences the networkperformance degrades. In the work, we have evaluated thePerformance of WMN under packet dropping on the basis oftheir throughput and Data packet loss.